Human development in an evolutionary perspective: A review - Ghanshyam Vatsa (AG Volumes, 2022)
"Evolutionary developmental psychology" is considered alongside other approaches that have sought to apply the evolutionary theory to a study of human behaviour, like sociobiology and more contemporary mainstream evolutionary psychology. An EDP perspective has the potential to provide a more nuanced understanding of "human ontogeny" by focusing on the "whys" of development, which, in turn, will help us better comprehend the "hows" and "whats" of development. In this study, we propose that learning more about the "whys" of development would help us learn more about the "hows" and "whos" of development. It is plausible to assume that there is a connection between ’phylogenies" and "ontogenetic" development due to the interdependence of biological, social, cognitive, and emotional elements that shape this development. ’Evolutionary developmental psychology" has been accepted in the scientific community because it offers a more complete picture of the maturation process.